Participación de las profesionales de enfermería en la promoción de salud de las mujeres gestantes que acuden a las unidades de salud del Área N° 2 - Jumbo Maza, Ingrid Elizabeth (2013)
According to the World Health Organization. The promotion and prevention activities used as a tool for health education, Education for health is a valuable strategy for the development of promotional programs that are used by medical personnel . In which priority plays a nurse because through participatory leadership allows pregnant integrated with prenatal pos , and give ongoing support on measures of health promotion , specific protection , emotional and family planning, leading to the successful completion of pregnancy. The Ministry of Health has, as one of its fundamental guidelines for the period 2002-2012, the implementation of a Model Comprehensive Health Care ( MAIS ) At national level we find that there is an increase of 80 % in 2012 unlike previous years was 55 % because they have increased health promotion programs for pregnant women by the government and is FREE MATERNITY AND HEALTHY CHILD CONTROL . The present research work regarding the Participation of nurses in promoting health of pregnant women, I conducted with nurses working in the center and sub- Health Area No. 2 “GUILLERMO GONZALEZ HUGO Loja CITY " .The type of study is detailed description because it made nursing professionals to promote health in pregnant women, and because quantitative data through tabular and we will be able to obtain percentages to interpret and analyze, the techniques used for data collection were: direct observation and unstructured interviews. From observation guides , held nursing staff daily activities , staff unprofessional Health Center No. 2 " HUGO GUILLERMO GONZALES " , care provided by the staff working at 14% never friendly , 18% never identified , 18 % never explains the procedures that you are having the patient , this gives a negative environment for mutual interaction of nurse / patient , to promote the health of pregnant women , 100 % of nursing staff education on healthy lifestyles for pregnant women , 93 % do not posconsulta to indicate the administration of iron and folic acid intake , 87 % does not indicate the administration of multivitamins during pregnancy , 85 % of nursing staff shows how to prepare the nipple of the mother , 73 % did not indicate on the pregnant woman prenatal should lead ; 23% is 3-4 servings of carbohydrates , meat and dairy , 17% 5-6 servings of carbohydrates , meats and dairy , according to data oriented staff not feeding properly . The 34 % of nursing staff never made educational presentations to the pregnant causing a negative impact on them that usually unaware of the processes to develop during this stage, 25% do not report on the laws for the mother . Interviews conducted with 11 professionals, it was stated that although it states that everything is done as said the MSP policy , professional practice , promoting healthy lifestyles through health education to pregnant women , leaves much to say either because direct work performed by non-professionals .